PEMBERDAYAAN PEREMPUAN DALAM MEMUTUS MATA RANTAI COVID-19 - Desy Dwi Cahyani; Rita Yulifah; Asworoningrum Yulindahwati; Lisa Purbawaning (Politeknik Kesehatan Kemenkes malang, 2021)
The COVID-19 pandemic has an impact on various sectors of life. During the COVID-19 pandemic, the suggestion to stay at home has had a positive impact on improving family communication, increasing attachment between family members, including childcare and increased ability to use. information Technology. New habitual practices that consistently make a person, family, group or community able to maintain personal health and play an active role in realizing public health in the face of the COVID-19 pandemic. The aim of this activity is Empowering Women in Breaking the Covid-19 Chain